The Bargaining Position of Women in Village Fund Management in Balee Inong - Zainal Putra4, T. Lembong Misbah5, Masrizal1, Partini2, Ishak Hasan3, (Opción, 2019)
The aim of the study is to investigate the bargaining position ofwomen in village fund management in Balee Inong. This study uses atype of field research with qualitative methods with the approach ofcontemporary feminist ethnography. As a result, 10 percent of villagefunds are allocated for women's activities from 90 villages in BandaAceh. This study concluded that the Balee Inong was involved inmanaging village funds both from the Regional Budget (APBD) andthe State Budget (APBN) and other sources of funds managed by thevillage.